Hay que matar a Lewis Winter - Mackay, Malcolm, 1982- (Nuevos tiempos (Madrid, Spain), 2016)
A twenty-nine-year-old man lives alone in his Glasgow flat. The telephone rings; a casual conversation, but behind this a job offer. The clues are there if you know to look for them. He is an expert. A loner. Freelance. Another job is another job, but what if this organization wants more? A meeting at a club. An offer. A target: Lewis Winter, a necessary sacrifice that will be only the first step in an all-out war between crime syndicates the likes of which hasn't been seen for decades. It's easy to kill a man. It's hard to kill a man well. People who do it well know this. People who do it badly find out the hard way. The hard way has consequences.